2020
DOI: 10.1016/j.jadohealth.2020.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Improving Adolescent Health: Translating Health Behaviour in School-aged Children Evidence Into Policy

Abstract: The Health Behaviour in School-aged Children (HBSC) study has informed the development and implementation of policy for children and adolescents for over three decades. The growing recognition that adolescence is a critical period for later health and well-being has highlighted the need for, and importance of timely and accurate data. Every 4 years, the HBSC study provides evidence on health behaviors, health outcomes, and social environments of boys and girls across Europe and North America. To maximize the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
0
6
0
2
Order By: Relevance
“…6,7 Data from the Health Behaviour in School-aged Children (HBSC) study, for example, enabled priority areas for action on adolescent health to be identified and led to system changes and targeted policy actions in areas including substance use and healthy lifestyles. 8 To meet the need for standardized surveillance data on children's weight status, the WHO Regional Office for Europe and 13 Member States established the WHO European Childhood Obesity Surveillance Initiative (COSI) in 2007. 9 In September 2020, the WHO Regional Committee for Europe endorsed a new European Programme of Work (EPW) for the period 2020-2025, proposing a vision for WHO's work in Europe that focuses on united action for better health.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Data from the Health Behaviour in School-aged Children (HBSC) study, for example, enabled priority areas for action on adolescent health to be identified and led to system changes and targeted policy actions in areas including substance use and healthy lifestyles. 8 To meet the need for standardized surveillance data on children's weight status, the WHO Regional Office for Europe and 13 Member States established the WHO European Childhood Obesity Surveillance Initiative (COSI) in 2007. 9 In September 2020, the WHO Regional Committee for Europe endorsed a new European Programme of Work (EPW) for the period 2020-2025, proposing a vision for WHO's work in Europe that focuses on united action for better health.…”
Section: Introductionmentioning
confidence: 99%
“…The HBSC has informed national and international policy related to adolescent health for over three decades, with specific examples outlined in a commentary by Budisavljevic et al [13]. This supplement issue highlights novel findings from the latest HBSC 2017e2018 survey, using data from 45 countries across Europe and North America.…”
Section: Discussionmentioning
confidence: 95%
“…The [6,10e12]. The final commentary by Budisavljevic et al [13] demonstrates the critical importance of how data can drive policy and encourage investment in the early adolescence phase of life course development.…”
mentioning
confidence: 99%
“…For the adolescent population, this includes the WHO Health Behaviour in School-Aged Children Study [27] and the European School Survey Project on Alcohol and Other Drugs (ESPAD) [28]. These are important monitoring tools, and data from them are seen as highly relevant for national policy planning [29]. These studies have only seen limited use as a platform for evaluating policy efforts, but they provide valid, comparable research instruments available in the Nordic languages that can easily be adopted for use in evaluation studies, and data that may be linked to relevant registries (subject to the relevant consents).…”
Section: The Way Forwardmentioning
confidence: 99%